FACTORS MOTIVATING STUDENTS TO CONTINUE USING YOUTUBE AS A LEARNING AID POST-COVID-19 PANDEMIC - Sukma Ningsih, Wahyu Meilia; Dedi I Inan; Rully N Wurarah; Obadja A Fenetiruma (Universitas Serang Raya, 2024)
During the COVID-19 pandemic, the process of teaching and learning had to be conducted online, such as through Zoom meetings, due to physical meeting restrictions, including in higher education. However, this was not entirely effective due to various factors, such as individual student learning preferences. To enhance comprehension, students utilized video-sharing platforms like YouTube, which, as it turns out, was effective. Hence, this study aims to investigate what factors motivate students (both school and university students) to continue using YouTube as a learning medium post-COVID-19 pandemic. A theoretical lens of the Expectation Confirmation Model is used with the addition of external variables: Perceived Herd and Parasocial Interaction. A total of 242 respondents from both educational levels in Manokwari Regency were obtained and analyzed using Partial Least Square - Structural Equation Modelling (PLS-SEM). The study's results explain that students experience satisfaction in using YouTube, which motivates them in Manokwari to continue using it as a learning medium post-COVID-19. This satisfaction is influenced by variables such as confirmation (C), perceived usefulness (PU), and perceived herd (PH). However, the PU factor's impact on continuance usage (CU) has a t-statistic value <1.96 and a p-value >0.05, indicating it lacks significant influence. There is also a rejection of the parasocial interaction (PI) variable's influence on satisfaction (S). Furthermore, the use of control variables such as age and gender has shown significant influence on this study, with research findings indicating that age and gender significantly impact satisfaction and continuance usage. Keywords: Control Variables, COVID-19, Expectation Confirmation Model, Parasocial Interaction, Perceived Herd, YouTube